A Forward Genetic Approach to Mapping a P-Element Second Site Mutation Identifies DCP2 as a Novel Tumor Suppressor in Drosophila melanogaster - Mishra, Rakesh (G3 (Bethesda), 2020)
The use of transposons to create mutations has been the cornerstone of Drosophila genetics in the past few decades. Second-site mutations caused by transpositions are often devoid of transposons and thereby affect subsequent analyses. In a P-element mutagenesis screen, a second site mutation was identified on chromosome 3, wherein the homozygous mutants exhibit classic hallmarks of tumor suppressor mutants, including brain tumor and lethality; hence the mutant line was initially named as lethal (3) tumorous brain [l(3)tb]. Classical genetic approaches relying on meiotic recombination and subsequent complementation with chromosomal deletions and gene mutations mapped the mutation to CG6169, the mRNA decapping protein 2 (DCP2), on the left arm of the third chromosome (3L). Thus the mutation was renamed as DCP2(l(3)tb). Fine mapping of the mutation further identified the presence of a Gypsy-LTR like sequence in the 5′UTR coding region of DCP2, along with the expansion of the adjacent upstream intergenic AT-rich sequence. The mutant phenotypes are rescued by the introduction of a functional copy of DCP2 in the mutant background, thereby establishing the causal role of the mutation and providing a genetic validation of the allelism. With the increasing repertoire of genes being associated with tumor biology, this is the first instance of mRNA decapping protein being implicated in Drosophila tumorigenesis. Our findings, therefore, imply a plausible role for the mRNA degradation pathway in tumorigenesis and identify DCP2 as a potential candidate for future explorations of cell cycle regulatory mechanisms.